Pelatihan Praktik Pengurusan Jenazah Sebagai Upaya Meningkatkan Pemahaman Keagamaan Di Kelurahan Tamaona: Program Pengabdian Mahasiswa KKN STAI Al Furqan: Pelatihan Praktik Pengurusan Jenazah Sebagai Upaya Meningkatkan Pemahaman Keagamaan Di Kelurahan Tamaona: Program Pengabdian Mahasiswa KKN STAI Al Furqan - Fitriani, Fitriani; Alief Hidayatullah, Muhammad; Khaerunnisa. A, St.; Lugiato, Lugiato; Rahayu, Asri; Sirajuddin, Muhammad; Karadona, Rosika Indri (Tasnim Journal for Community Service, 2025)
Managing the corpse is a fardhu kifayah obligation for Muslims which includes the process of washing, shrouding, praying and burying the corpse according to the Shari'a. However, there are still many people who do not understand the procedures for handling corpses properly. Therefore, implementing Practical Training on Handling Bodies in Tamaona Village is a strategic step in increasing the community's religious understanding. This research uses a qualitative descriptive method with a case study approach. Information is collected through interviews, observation and documentation. The research results show that this training contributes to increasing religious understanding, practical skills in handling corpses, and fostering social awareness in society. However, there are several obstacles in its implementation, such as limited facilities and teaching staff. Therefore, it is proposed that this training be carried out periodically with further support from related parties.